Post Operative Management in Intensive Care of Obstructive Jaundice caused by Choledocholithiasis: A Case Report - Liliriawati Ananta Kahar; Wiwi Monika Sari (Indonesian Journal of Rheumatology, 2023)
Introduction: Gallstones are a very common problem in the global population. 10%-25% of affected people may have specific symptoms, and 1%-2% of them may experience major complications. Case presentation: 83-year-old female patient complained of yellow in her eyes and skin. Patients also felt pain in the right upper abdomen. Laboratory examination revealed increased bilirubin serum. Abdominal Ultrasound examination showed Obstruction of the Bilier Ductus caused by a stone at ductus sisticus and sludge of the gallbladder. The patient was diagnosed with Jaundice obstruction caused by obstruction of the bile ducts due to a stone at the ductus sisticus with a history of nephrectomy, Hypertension, and type 2 diabetes. The patient underwent Laparoscopic cholecystectomy, ERCP, and stent biller, After the procedure, the patient was admitted to the intensive care unit. Conclusion: Understanding the patient's comprehensive medical and surgical history is fundamental in understanding the postoperative patient in the intensive care unit. Adequate resuscitation is necessary for good clinical perfusion and physiological stability of the patient.